2016
DOI: 10.2147/ott.s98807
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of differentially expressed proteins in prostate cancer based on proteomics data

Abstract: We mined the literature for proteomics data to examine the occurrence and metastasis of prostate cancer (PCa) through a bioinformatics analysis. We divided the differentially expressed proteins (DEPs) into two groups: the group consisting of PCa and benign tissues (P&b) and the group presenting both high and low PCa metastatic tendencies (H&L). In the P&b group, we found 320 DEPs, 20 of which were reported more than three times, and DES was the most commonly reported. Among these DEPs, the expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 84 publications
3
15
0
Order By: Relevance
“…Another group of proteins decreased in the PCa tissues was related to blood microparticles, which influence the complement and coagulation cascades and platelet degranulation. These bioinformatic results are very similar to previous proteomics studies conducted in PCa (31)(32)(33). In fact, these three protein groups, including the mitochondrial proteins, extracellularrelated proteins, and blood microparticle proteins, are known to be highly related to the occurrence of cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Another group of proteins decreased in the PCa tissues was related to blood microparticles, which influence the complement and coagulation cascades and platelet degranulation. These bioinformatic results are very similar to previous proteomics studies conducted in PCa (31)(32)(33). In fact, these three protein groups, including the mitochondrial proteins, extracellularrelated proteins, and blood microparticle proteins, are known to be highly related to the occurrence of cancer.…”
Section: Discussionsupporting
confidence: 88%
“…org) also identifies Staufen1 as a prognostic factor in human prostate cancer where survival rates decrease in patients with high Staufen1 expression (N = 99) compared to those with low Staufen1 expression (N = 395) (Protein Atlas; Stau1). 1 These findings are in agreement with the cell line data presented above and indicate that Staufen1 is also increased in human PC tumours.…”
Section: Staufen1 Is Increased In Human Prostate Cancersupporting
confidence: 92%
“…Prostate cancer (PC) is one of the most common malignant cancers with the second highest rate of mortality in men worldwide [1][2][3][4]. Despite improved scientific knowledge surrounding the underlying molecular mechanisms and risk factors associated with PC, prognosis remains poor for advanced PC [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the cystic fluid of PCLs, Fibrinogen Alpha chain (FGA), fibrinogen beta chain (FGB), and fibrinogen gamma chain (FGG) were markedly elevated in MCN. They have been reported to elevate in prostate cancer, lung cancer, hepatocellular carcinoma, pancreatic cancer, infectious diseases, and myocardial infarction [37, 38]. Ghezzi reported that plasma fibrinogen level might be a potential index to predict prognosis, improving the early diagnosis of endometrial cancer and optimize the treatment schedule [39].…”
Section: Discussionmentioning
confidence: 99%